logo

Ask Questions, Get Answers

X
 
Home  >>  EAMCET  >>  Mathematics

$\overrightarrow {u}=\overrightarrow {a}-\overrightarrow {b},\overrightarrow {v}=\overrightarrow {a}+\overrightarrow {b},| \overrightarrow {a} | =| \overrightarrow {b} |=2 => | \overrightarrow {u} \times \overrightarrow {v} |=$

\[\begin {array} {1 1} (1)\;2 \sqrt {16-(\overrightarrow {a}.\overrightarrow {b})^2} & \quad (2)\; \sqrt {16-(\overrightarrow {a}.\overrightarrow {b})^2} \\ (3)\;2 \sqrt {4-(\overrightarrow {a}.\overrightarrow {b})^2} & \quad (4)\; \sqrt {4-(\overrightarrow {a}.\overrightarrow {b})^2} \end {array}\]

1 Answer

$(1)\;2 \sqrt {16-(\overrightarrow {a}.\overrightarrow {b})^2}$
answered Nov 7, 2013 by pady_1
 

Related questions

...